The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/tri.12067
|View full text |Cite
|
Sign up to set email alerts
|

Kidneys from uncontrolled donors after cardiac death: which kidneys do worse?

Abstract: SummaryKidneys from uncontrolled donors after cardiac death (DCD) expand the donor pool, but are associated with more primary nonfunction (PNF) and delayed graft function (DGF) compared with more conventional donor kidneys. It remains unclear, which factors influence outcome of uncontrolled donation. Therefore, we studied which donor, graft, and recipient characteristics are associated with PNF in a large cohort study. The association between different characteristics and short-term graft function was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…7 In our cohort, roughly 60 uDCD kidneys and 170 cDCD were machine perfused between 2002 and 2012. Management of machine perfusion of DCD was done as described by Hoogland et al 4,7 Viability testing was not used to determine organ suitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In our cohort, roughly 60 uDCD kidneys and 170 cDCD were machine perfused between 2002 and 2012. Management of machine perfusion of DCD was done as described by Hoogland et al 4,7 Viability testing was not used to determine organ suitability.…”
Section: Discussionmentioning
confidence: 99%
“…However, lately, there has been growing interest in the potential of uDCD kidneys. 4-7 In some European countries like Spain and France, transplantation with uDCD kidneys is a more common practice, and promising results with uDCD have been reported. 8-15 After the pioneering work of the Maastricht Transplantation Center, the practice of transplanting uDCD kidneys has been implemented throughout all Dutch transplant centers.…”
mentioning
confidence: 99%
“…Pieter Hoogland et al 8 reported the outcome of the earliest series of uDCD kidney transplants (n = 135) from 1981 to 2009 in the Netherlands: the DGF rate was 61% and the PNF rate 22%. All kidneys were flushed in situ with HTK solution and the majority preserved by HMP with Belzer UW solution from 1985.…”
Section: Kidney Preservation Techniquesmentioning
confidence: 99%
“…Evidence from the United States, Australia, the United Kingdom, and Europe has demonstrated that shipping kidneys is safe with CITs of up to 16 h. However, this increases the risk of DGF, which may reduce graft and patient survival and increase incidences of acute rejection. 12,[34][35][36][37] Deceased Donor Kidney Transplantation Rates of DGF in deceased donor kidney transplantation range from 10% in standard donation after brain death (DBD) kidneys to 93% in uDCD 4,7,8,10,[16][17][18][19][20][21][22][23]27,38 (Table 1). The outcomes of graft and patient survival at 1 y are good but slightly lower in comparison to living donor kidneys.…”
Section: Kidney Donors Live Donor Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation